The Role of Psychotrop Medicines in Food Aspiration: A Case Report - Çoban, İsmail; Mutlu, Emre (The Bulletin of Legal Medicine, 2023)
Although swallowing disorders are quite common in psychiatric patients and especially in patients with schizophrenia, they have not been adequately studied. Swallowing disorders are an important source of morbidity and mortality in patients with schizophrenia as a result of acute asphyxia resulting from airway obstruction or an insidious aspiration and pneumonia. Most swallowing disorders in schizophrenia are attributed to two main causes: The changes in eating and swallowing due to the disease itself and the effects of psychotropic drugs. Behavioural changes related to the illness include eating too fast or taking in inappropriately large amounts of food. Treatment-related problems are most often associated with drug-induced extrapyramidal side effects, including drug-induced parkinsonism, dystonia, and tardive dyskinesia. In this case report, it is aimed to share the psychotropic drugs detected in a schizophrenic patient who developed mechanical asphyxia due to food aspiration and to examine their possible effects on food aspiration.
Keywords: Dysphagia, Antipsyc, Aspiration, Dry mouth